Synthesis of Rutile-Rich Corundum/Rutile Functionally-Graded Materials with Different Precursors - Suminar Pratapa; Khusnul Umaroh; Frissa Erina Herdiyanti (Institut Teknologi Bandung, 2011)
Synthesis of corundum/rutileFGMS had been done with five repeated infiltrations. Preforms were made from corundum powder which were presintered at 1000°C for 1 hour to obtain green body porosity of around 54%. The infiltration was performed by repeatedly fully immersing the preforms in TiCl3 and Ti(SO4)2 solutions (approximately 20% w/v). The infiltrated preforms were then calcined at 1200°C for 2 hours. Phase characterisation using X-Ray Diffractometry (XRD) indicated that peak intensity of rutile increased with number of infiltration. Further observation showed that maximum gain of rutile was obtained from preforms which were fully immersed in the TiCl3-containing solution. Phase composition study at various depths for the TiCl3-containing samples using XRD showed that the content of rutile decreased with depth from 54% at the surface, 32% at 0.2 mm, 20% at 0.4 mm and 17% at 0.6 mm, while that for corundum increased complementarily. The phase composition results implied that synthesis of rutile-rich corundum/rutile functionally-graded materials has been successful using such precursor with multiple infiltration.